2017
DOI: 10.1038/s41598-017-07034-w
|View full text |Cite
|
Sign up to set email alerts
|

Predicting hair cortisol levels with hair pigmentation genes: a possible hair pigmentation bias

Abstract: Cortisol concentrations in hair are used to create hormone profiles spanning months. This method allows assessment of chronic cortisol exposure, but might be biased by hair pigmentation: dark hair was previously related to higher concentrations. It is unclear whether this association arises from local effects, such as increased hormone extractability, or whether the association represents systemic differences arising from population stratification. We tested the hypothesis that hair pigmentation gene variants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…These findings are mostly contradictory to previously reported findings when hair cortisol was mainly reported not to be affected by hair color [7,26]. But there are also newer large studies that support our findings that darker hair color was related to higher cortisol levels [9,21] and a recent study indicated that genetic variants associated with darker hair color predict higher hair cortisol concentrations [27]. It was hypothesized by other research groups that the lack of association between hair color and cortisol is explained by the fact that cortisol is incorporated independently of the melanin as it is known for acidic and neutral substances.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are mostly contradictory to previously reported findings when hair cortisol was mainly reported not to be affected by hair color [7,26]. But there are also newer large studies that support our findings that darker hair color was related to higher cortisol levels [9,21] and a recent study indicated that genetic variants associated with darker hair color predict higher hair cortisol concentrations [27]. It was hypothesized by other research groups that the lack of association between hair color and cortisol is explained by the fact that cortisol is incorporated independently of the melanin as it is known for acidic and neutral substances.…”
Section: Discussioncontrasting
confidence: 99%
“…Although often discussed as a potential issue 41,42 no one study admitted to including hair follicles in their hair samples and all but six papers 5,34,4346 explicitly described methods designed to ensure samples being free of follicles. It has been theorized that the color of a hair can influence the GC content 47 , however the results are inconsistent 10 and hair color is rarely reported. We consequently did not attempt to extract information on this.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, chemical analysis of eumelanin and pheomelanin in dog hair sample or analysis of pigment genes in fundamental studies can help to objectively evaluate differences in HCC in dog hair samples. For example, in humans, the effect of hair pigmentation on HCC was studied by evaluating hair pigmentation genes 53 .…”
Section: Discussionmentioning
confidence: 99%